Food applications of natural antimicrobial compounds - Del Nobile, Matteo Alessandro; Lucera, Annalisa; Costa, Cristina; Conte, Amalia (Frontiers in Microbiology, 2012)
In agreement with the current trend of giving value to natural and renewable resources, the use of natural antimicrobial compounds, particularly in food and biomedical applications, becomes very frequent. The direct addition of natural compounds to food is the most common method of application, even if numerous efforts have been made to find alternative solutions to the aim of avoiding undesirable inactivation. Dipping, spraying and coating treatment of food with active solutions are currently applied to product prior to packaging as valid options. The aim of the current work is to give an overview on the use of natural compounds in food sector. In particular, the review will gather numerous case-studies of meat, fish, dairy products, minimally processed fruit and vegetables and cereal-based products where these compounds found application.